2020
DOI: 10.1002/1878-0261.12741
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine subtypes of small cell lung cancer differ in terms of immune microenvironment and checkpoint molecule distribution

Abstract: Small cell lung cancer (SCLC) has recently been subcategorized into neuroendocrine (NE)‐high and NE‐low subtypes showing ‘immune desert’ and ‘immune oasis’ phenotypes, respectively. Here, we aimed to characterize the tumor microenvironment according to immune checkpoints and NE subtypes in human SCLC tissue samples at the protein level. In this cross‐sectional study, we included 32 primary tumors and matched lymph node (LN) metastases of resected early‐stage, histologically confirmed SCLC patients, which were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 61 publications
1
58
0
Order By: Relevance
“…36 This categorization has major clinical impact, as the two phenotypes are anticipated to respond differently to targeted therapeutics and ICIs. 37,38 Of note, another example of NE heterogeneity was described by Gazdar et al 39,40 in 1985 based on the in vitro and in vivo behavior of SCLC cells. The "classic" phenotype is associated with typical morphology, high expression of NE markers, and non-adherent growth pattern in cell cultures.…”
Section: Tumor Heterogeneity In Sclc Neuroendocrine (Ne) Subtypesmentioning
confidence: 95%
See 1 more Smart Citation
“…36 This categorization has major clinical impact, as the two phenotypes are anticipated to respond differently to targeted therapeutics and ICIs. 37,38 Of note, another example of NE heterogeneity was described by Gazdar et al 39,40 in 1985 based on the in vitro and in vivo behavior of SCLC cells. The "classic" phenotype is associated with typical morphology, high expression of NE markers, and non-adherent growth pattern in cell cultures.…”
Section: Tumor Heterogeneity In Sclc Neuroendocrine (Ne) Subtypesmentioning
confidence: 95%
“…NE-high tumors with the immune desert phenotype are associated with decreased immune cell (CD8 + effector T cells primarily) infiltration compared to NE-low tumors. 36,38 Expressions of indoleamine 2,3-dioxygenase (IDO) and poliovirus receptor (PVR), which are both important factors of the SCLC immune microenvironment, are also significantly lower in NE-high tumors (versus NE-low tumors). 38,[83][84][85] In addition, these tumors are associated with low T cell immunoglobulin and mucin domain-3 (TIM3) levels as well.…”
Section: Immunotherapymentioning
confidence: 99%
“…Current studies have found that the development of cancer are not only dependent on tumor cell characteristics but are also affected by the interaction with infiltrated immunocytes [ 30 , 31 ]. The tumors with higher immune cells and mediators proportion were proved to be more effective to the immune treatment [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…IDO activity is a hallmark of tryptophan depletion and suppression of Chlamydia growth in cell cultures and mice. Furthermore, IDO activity is associated with several pulmonary diseases, including lung cancer [ 37 ]. Sputum IDO activity was enhanced in an IL-10 dependent manner in asthmatic patients receiving ICSs; the ICSs increased IL-10 secretion from macrophages in parallel with IDO activity, indicating that ICS use could generate IDO activity through IL-10 production [ 38 ].…”
Section: Discussionmentioning
confidence: 99%